Effectiveness of PjBL Worksheet Based on Local Potential to Improve Critical and Creative Thinking Skills of Phase E High School Students - Tasya Novian Indah Sari; Anna Rakhmawati; Hanifa Rizky Rahmawati (Journal of Innovation in Educational and Cultural Research, 2025)
Involving local potential as teaching material content is an effort to create more contextual learning and introduce local potential to students. This study aimed to determine the effectiveness of the PjBL-Worksheet based on the regional potential of Gandong River in improving critical and creative thinking skills. The research method is a quasi-experimental nonrandomized control class pretest-posttest design. The study was conducted in January-March 2024. The research population was students of Phase E of SMA 1 Sukomoro, Indonesia. The research sampling technique was cluster random sampling, and the research sample was students of classes Phase E.1 and E.5. The method of collecting data on critical and creative thinking skills was using a test technique. The instrument used to collect data was valid and reliable essay questions. The data were analyzed descriptively and using one-way MANOVA tests. The result of 0.00 0.05 means that applying the PjBL Worksheet based on the local potential of Sungai Gandong was practical in simultaneously improving students' critical and creative thinking skills. The results of further tests showed that the treatment given had a simultaneous effect on critical thinking skills by 68.3% and creative thinking by 62.3%.